Dampak Oligopoli terhadap Masyarakat dan Pertumbuhan Industri - Ikke Adelia Amanda; Muhammad Yasin (Pajak dan Manajemen Keuangan, 2025)
Oligopoly is a market structure controlled by a small number of companies that dominate market share. This research examines the impact of oligopoly on society and industrial growth, with a focus on economic, social and structural aspects. Economically, oligopoly can reduce price competition and lead to price regulation that is detrimental to consumers. Socially, this market structure can exacerbate economic inequality and limit the opportunities of small entrepreneurs. In terms of industrial growth, oligopoly can provide stability, but also reduce incentives for innovation. This research also discusses the role of government policies, such as antitrust regulations, in reducing the negative impacts of oligopolies. This research will also discuss the role of government policy in regulating oligopolies to ensure that the negative impacts of this market structure can be minimized. Policies such as antitrust and price regulation need to be implemented to maintain a balance between industrial stability and societal welfare.